PENGARUH PROFESIONALISME, PENGETAHUAN MENDETEKSI KEKELIRUAN, DAN ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS AKUNTAN PUBLIK - Marini - Marini (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2017)
Abstract Relevance and reliability are the two primary qualities that make accounting information useful for decision making. Therefore, an audit of financial statement is necessary, especially for a Tbk company. To maintain the trust of clients and users of financial statements, the public accountants should to have sufficient competence, such as professionalism, knowledge to detects errors, professional ethics and judgement of materiality level. Purpose of this study is to provide empirical evidence about affect of professionalism, knowledge to detect errors, and professional ethics to the public accountants judgement of materiality level with partial and simultaneous. Population in the study is a public accountant who worked at a Public Accounting Firm in South Jakarta. Sampling technique using convenience sampling method. Data obtained by questionnaire survey completed by the public accountant with 98 respondents from 9 Public Accounting Firm with primary data types. Design is causal research. The results showed that : 1) Professionalism affect of the judgement of materiality level. 2) Knowledge to detect errors did not affect of the judgement of materiality level. 3) Professional ethics affect of the judgement of materiality level. 4) Professionalism, knowledge to detect errors, and professional ethics affect of the judgement of materiality level.                                                                Keyword :    Professionalism, Knowledge to detect errors, Professional ethics and Judgment of materiality level.